Internal Digitalization and Tax-efficient Decision Making - Daniel Klein; Christopher Ludwig; Katharina Nicolay (ZBW - Leibniz Information Centre for Economics, 2021)
This paper investigatesthe effect of firms' internal digitalization on the performance of business support functions such as the tax department. We put forward a novel, micro-level IT sophistication index based on a survey monitoring European firms' digital infrastructure. Following the objective function of maximizing after-tax returns, we measure tax-efficient decisions in terms of minimizing the firm's worldwide tax burden. We show that internal digitalization boosts firms' ability to relocate income to tax-favored jurisdictions. We confirm this result using two plausibly exogenous shocks. First, we exploit a business software supply shock and provide evidence that the adoption of digital technologies enhances efficient crossborder tax planning. Second, using an event study design, we show that digitalized firms promptly adjust reported profits in response to income shifting incentive shocks. Overall, we show that digital infrastructure is a crucial foundation for timely, data-driven decision making and increases support functions' performance.
Keywords: O33; L25; H25; H26; K34; 330; Digital Transformation; Digitalization; Firm Performance; Decision Making; Information Technology; Tax Planning